City dynamics and complexity: sustainability or ‘bust’ - Abdul Samad Hadi,; Abdul Hadi Harman Shah,; Shaharudin Idrus, (Environmental Management Society, Malaysia, 2009)
On behalf of the Institute for Environment and Development (LESTARI), Universiti Kebangsaan Malaysia (UKM) I would like to extend our warmest welcome to all those present in this Round Table Dialog on MODELLING THE COMPLEXITY OF LIVABLE URBANIZATION this morning. This meeting is exceptionally honored by the presence of Professor Dr. Michael Batty from the University of College London, who, from this quote from a commentary of his book Cities and Complexity: Understanding Cities with Cellular Automata, Agent-Based Models, and Fractals (2005) published by MIT press - that ‘unites into an integrated whole path-breaking methods in urban research centered on ideas of non-linear dynamic emergence and self-organization (Berry 2005), is the leading guru of urban complexity modeling in the world. We are also honored by the presence of Associate Professor Dr. Ray Wyatt, from the University of Melbourne, Australia who is also working on aspects of city complexity, and has been visiting the Institute from time to time. We are equally honored by the presence and willingness of our local colleagues who have been spending their productive research lives on the city-unraveling its mystery and importance, and to come to the dialog to share with us their experiences today. We are equally honored to have with us participants from the academia, the non-governmental organizations and representatives of associated government departments, who are practitioners in city issues in the country